Japan's R&D strategy reconsidered departure from the manageable risks - Baba, Yasunori (Technovation)
The authors describe how Japanese organizations are moving from R&D projects conditioned by a fixed manageable risk to take into account the more flexible strategies of a changing market : 'extraordinary' innovations have now become the R&D target for many Japanese firms.